Children of Communism: The Former Party Membership and Demand for Redistribution - Alexander Libman; Olga Popova (Institute of Labor Economics (IZA), 2022)
The paper looks at the persistence of egalitarian norms in post-Communist societies by focusing on the former members of the Communist parties in Central and Eastern Europe (CEE) and Russia and their children. Using the individual-level survey data, we show that there are striking differences between Russia and the CEE countries in this respect. While in the CEE both former members of the Communist parties and their children have stronger preferences for redistribution than the rest of the population, in Russia former CPSU members do not exhibit stronger preferences for redistribution – at the same time, their children support redistribution.
Keywords: D31; I30; N00; P36; P52; 330; Communist Party; inequality; redistribution; Russia; Visegrad group